2014
DOI: 10.1111/bjc.12040
|View full text |Cite
|
Sign up to set email alerts
|

A compassionate‐focused therapy group approach for acute inpatients: Feasibility, initial pilot outcome data, and recommendations

Abstract: This is the first attempt to explore the effects of a CFT-informed approach in acute mental health settings. These groups were well received by staff and patients, with some therapeutic impact despite being comparatively short and set against the background of a busy inpatient ward. These groups can be open and transdiagnostic, with stand-alone topics and practices having positive impacts on distress and calmness. Future studies need to focus on adapting content and pacing for this group of people based on ong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 17 publications
3
61
0
Order By: Relevance
“…So, one question is: could the introduction of a few (4) sessions of CFT that covers areas such as helping people consider why our brains can give us so much trouble (and that is not our fault), the nature of mindfulness and attention, understanding and cultivating compassion, and the development of specific imaging practices, be helpful for this troubled and heterogeneous group? Heriot‐Maitland, Vidal, Ball and Irons () set out to explore a short CFT informed intervention in terms of feasibility in the busy ward context, patient acceptability and effectiveness. Importantly, they found that clients on acute units, who could be in high states of distress, could nonetheless understand the model and gain benefit from the insights it offered and some of the compassion practices.…”
mentioning
confidence: 90%
“…So, one question is: could the introduction of a few (4) sessions of CFT that covers areas such as helping people consider why our brains can give us so much trouble (and that is not our fault), the nature of mindfulness and attention, understanding and cultivating compassion, and the development of specific imaging practices, be helpful for this troubled and heterogeneous group? Heriot‐Maitland, Vidal, Ball and Irons () set out to explore a short CFT informed intervention in terms of feasibility in the busy ward context, patient acceptability and effectiveness. Importantly, they found that clients on acute units, who could be in high states of distress, could nonetheless understand the model and gain benefit from the insights it offered and some of the compassion practices.…”
mentioning
confidence: 90%
“…Integrating qualitative and quantitative data in a study of a compassion focused group, for example, allowed Heriot‐Maitland et al. () to understand the activation of positive affect and a sense of common humanity among a subset of group members. Researchers were able to attend to unique aspects of group intervention, like compassion (Heriot‐Maitland et al., ), gardening as an intervention (Swank & Shin, ), and music therapy (Bensimon et al., ; Carr et al., ; Grocke et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…CFT has shown promising early outcomes in clinical settings with individuals (Ashworth et al, 2011;Mayhew & Gilbert, 2008) and in groups (Braehler et al, 2013;Heriot-Maitland et al, 2014).…”
Section: Compassion-based Interventionsmentioning
confidence: 99%
“…CFT interventions have demonstrated improvements in depression and anxiety in specialist community mental health services (Gilbert & Proctor, 2006;Judge et al, 2012). CFT interventions have also been shown to lead to improvements in symptoms for those with a diagnosis or symptoms of: Post Traumatic Stress Disorder (Beaumont et al, 2012); eating disorder (Gale et al 2012); personality disorder (Lucre & Corten, 2012); and schizophrenia or psychosis (Braehler et al, 2013;Heriot-Maitland et al, 2014;Laithwaite et al, 2009;Mayhew & Gilbert, 2008). CFT interventions have been delivered individually or in groups.…”
Section: Evidence For Cftmentioning
confidence: 99%